2014
DOI: 10.1111/1755-6724.12176
|View full text |Cite
|
Sign up to set email alerts
|

New Material of Zhenyuanopterus (Pterosauria) from the Early Cretaceous Yixian Formation of Western Liaoning

Abstract: A new partial specimen of Zhenyuanopterus from the Lower Cretaceous Yixian Formation of Beipiao city, Liaoning Province is described. This specimen is slightly larger than half the size of the holotype. Although it is not complete, it provides new information on Zhenyuanopterus both in taxonomy and ontogeny: the total number of the caudal vertebrae is 15; the forelimb is more robust than the hindlimb; the growth rate of the humerus and femur is constant, and their ratio is about 1. Compared with the holotype, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The Yixian Formation of Northeastern China has yielded various fossilized animals and plants [ 3 , 4 , 5 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], and stratigraphers have intensively studied the formation [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Although the age of the formation used to reach up to the Jurassic, recent works converge on a general consensus of approximately 125 Ma (Barremian-Aptian, Lower Cretaceous) [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Yixian Formation of Northeastern China has yielded various fossilized animals and plants [ 3 , 4 , 5 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], and stratigraphers have intensively studied the formation [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Although the age of the formation used to reach up to the Jurassic, recent works converge on a general consensus of approximately 125 Ma (Barremian-Aptian, Lower Cretaceous) [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…3). Boreopterus cuiae and Zhenyuangopterus longirostris possess slender, elongated teeth, interpreted to have trapped small aquatic organisms before straining and swallowing (Wang & Zhou, 2006;Witton, 2013;Teng et al, 2014).…”
Section: (8) Ornithocheiridaementioning
confidence: 99%
“…Trofimov (1978) described the lower dental formula of Gobiconodon as 3.1.4.5 and this was followed by others who considered the antemolariforms of the genus to comprise an enlarged incisor, a canine and three to four premolariforms (Jenkins and Schaff 1988;KielanJaworowska and Dashzeveg 1998;Maschenko and Lopatin 1998;Li et al 2003;Kielan-Jaworowska et al 2004). Meng et al (2005) challenged this and concluded that the lower dental formula of gobiconodontids is 2.1.2 -3.5, a view later accepted by Yuan et al (2009). Rougier et al (2007) proposed another interpretation, 3.1.2.5, but here we follow Meng et al (2005).…”
Section: Introductionmentioning
confidence: 55%
“…Meng et al (2005) challenged this and concluded that the lower dental formula of gobiconodontids is 2.1.2 -3.5, a view later accepted by Yuan et al (2009). Rougier et al (2007) proposed another interpretation, 3.1.2.5, but here we follow Meng et al (2005).…”
Section: Introductionmentioning
confidence: 55%